Measurement of compartment elasticity using pressure related ultrasound: a method to identify patients with potential compartment syndrome - Sellei, R. M; Hingmann, S. J; Kobbe, P; Weber, C; Grice, J. E; Zimmerman, F; Jeromin, S; Gansslen, A; Hildebrand, F; Pape, H. C (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2015)
PURPOSE OF THE STUDY Decision-making in treatment of an acute compartment syndrome is based on clinical assessment, supported by invasive monitoring. Thus, evolving compartment syndrome may require repeated pressure measurements. In suspected cases of potential compartment syndromes clinical assessment alone seems to be unreliable. The objective of this study was to investigate the feasibility of a non-invasive application estimating whole compartmental elasticity by ultrasound, which may improve accuracy of diagnostics. MATERIAL AND METHODS In an in-vitro model, using an artificial container simulating dimensions of the human anterior tibial compartment, intracompartmental pressures (p) were raised subsequently up to 80 mm Hg by infusion of saline solution. The compartmental depth (mm) in the cross-section view was measured before and after manual probe compression (100 mm Hg) upon the surface resulting in a linear compartmental displacement (Δd). This was repeated at rising compartmental pressures. The resulting displacements were related to the corresponding intra-compartmental pressures simulated in our model. A hypothesized relationship between pressures related compartmental displacement and the elasticity at elevated compartment pressures was investigated. RESULTS With rising compartmental pressures, a non-linear, reciprocal proportional relation between the displacement (mm) and the intra-compartmental pressure (mm Hg) occurred. The Pearson's coefficient showed a high correlation (r2 = -0.960). The intraobserver reliability value kappa resulted in a statistically high reliability (κ = 0.840). The inter-observer value indicated a fair reliability (κ = 0.640). CONCLUSIONS Our model reveals that a strong correlation between compartmental strain displacements assessed by ultrasound and the intra-compartmental pressure changes occurs. Further studies are required to prove whether this assessment is transferable to human muscle tissue. Determining the complete compartmental elasticity by ultrasound enhancement, this application may improve detection of early signs of potential compartment syndrome. Key words: compartment syndrome, intra-compartmental pressure, non-invasive diagnostic, elasticity measurement, elastography.
Keywords: Reproducibility of Results; biologické modely; ROC křivka; Elasticity Imaging Techniques; Elasticity; Humans; lidé; pružnost; syndrom předního tibiálního kompartmentu; tlak; reprodukovatelnost výsledků; Models, Biological; elastografie; Pressure; ROC Curve; Anterior Compartment Syndrome